CyberKnife for the management of Cushing's disease: our institutional experience and review of literature. (3rd September 2021) - Abdali, Ashraf; Kalinin, Pavel L.; Trunin, Yuriy Y.; Astaf'Eva, Ludmila E.; Shkarubo, Alexey N.; Chmutin, Gennady E.; Chavda, Vishal; Golanov, Andrey; Abdali, Badshazar; Chernov, Ilya V.; Vats, Atul; Chaurasia, Bipin
Abstract: Introduction: Surgery is the primary treatment for Cushing's disease(CD). In cases with no biochemical remission after surgical resection or when recurrence occurs after a period of remission stereotactic radiosurgery (SRS) is used as alternative/adjuvant treatment. The aim of this study is to demonstrate the effectiveness of SRS and FSRS(Fractionated stereotactic radiosurgery) for the treatment of CD in a long term follow up. Methods: This is a retrospective study in which 41 patient (36 females and 5 males) who underwent surgery for CD from 2009 to 2019 were included. Out of 41 cases, 34 cases had microadenomas while 7 had macroadenomas. These patients had recurrence or persistence of hypercortisolism post-operatively. After multidisciplinary evaluation, these patients were treated by CyberKnife (SRS & FSRS). Results: Remission rate in our study was 60.97% with a median follow up period of 79.03 months. The median time to biochemical remission was 14 months. Tumour growth control was achieved in 95.12%. Hypopituitarism of different axes was seen in 34.14% patients. Secondary hypothyroidism was the most common pituitary insufficiency (34%) followed by secondary hypogonadism in 17%. Conclusion: CyberKnife radiosurgery and hypofractionated radiosurgery can be used as an adjuvant treatment in patient with active disease and no biochemical remission after one or multiple surgical resections. Risk of radiation induced hypopituitarism and other complication is relatively low 34.14% and tumour growth control is significantly higher.